Analysis of miRNAs in the Heads of Different Castes of the Bumblebee Bombus lantschouensis (Hymenoptera: Apidae) - Meijuan Liu; Jiaxing Huang; Guangshuo Zhang; Xiaofeng Liu; Jiandong An (Insects, 2019)
Bumblebees are important insect pollinators for many wildflowers and crops. MicroRNAs (miRNAs) are endogenous non-coding small RNAs that regulate different biological functions in insects. In this study, the miRNAs in the heads of the three castes of the bumblebee Bombus lantschouensis were identified and characterized by small RNA deep sequencing. The significant differences in the expression of miRNAs and their target genes were analyzed. The results showed that the length of the small RNA reads from males, queens, and workers was distributed between 18 and 30 nt, with a peak at 22 nt. A total of 364 known and 89 novel miRNAs were identified from the heads of the three castes. The eight miRNAs with the highest expressed levels in males, queens, and workers were identical, although the order of these miRNAs based on expression differed. The male vs. queen, male vs. worker, and worker vs. queen comparisons identified nine, fourteen, and four miRNAs with significant differences in expression, respectively. The different castes were clustered based on the differentially expressed miRNAs (DE miRNAs), and the expression levels of the DE miRNAs obtained by RT-qPCR were consistent with the read counts obtained through Solexa sequencing. The putative target genes of these DE miRNAs were enriched in 29 Gene Ontology (GO) terms, and catalytic activity was the most enriched GO term, as demonstrated by its association with 2837 target genes in the male vs. queen comparison, 3535 target genes in the male vs. worker comparison, and 2185 target genes in the worker vs. queen comparison. This study highlights the characteristics of the miRNAs in the three B. lantschouensis castes and will aid further studies on the functions of miRNAs in bumblebees.